(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The development of nanoparticle-based drug delivery systems (NDDS) has become a significant tool for addressing the problems associated with drugs that are not readily soluble in water and, as a result, have restricted bioavailability due to poor dissolution and permeability. NDDS, which include liposomes, polymeric nanoparticles, nanoemulsions, nanohydrogels, inorganic carriers, dendritic polymers, and nanocrystals, are used in order to enhance the solubility of medications, as well as their stability, controlled release, and targeted administration. These NDDS do not alter the chemical structure of the medicine in any way, shape, or form. These systems are able to improve absorption, extend circulation, and reduce systemic toxicity by utilizing nanoscale features such as large surface area, surface functionalization, and reactivity to both internal and external stimuli. These features are utilized in order to achieve these goals. Nanocrystal technology, for example, is a versatile approach that may be used for intravenous, parenteral, and oral administration. This is because it boosts bioavailability, saturation solubility, and dissolving rate. Megestrol acetate, sirolimus, and fenofibrate are a few examples of marketed medications that demonstrate how these strategies have been developed and used successfully in translation. In conclusion, NDDS is an exciting new invention that has the potential to change targeted and combination treatments by boosting both the efficacy of the therapy and the patient’s compliance with the treatment requirements.